The devil is in the details: Problems in DNA barcoding practices indicated by systematic evaluation of insect barcodes - Cheng, Zhentao; Li, Qiang; Deng, Jun; Liu, Qian; Huang, Xiaolei (Frontiers in Ecology and Evolution, 2023)
In recent years, as a rapidly developing taxonomy tool, DNA barcoding has proved its value in species identification and the discovery of cryptic diversity. The number of barcoding sequences of various species continues to grow in the GenBank and BOLD databases; however, the accuracy of sequences and related raw information in public repositories is often questionable. In the present study, based on a dataset of 68,089 Hemiptera COI barcode sequences covering 3,064 species, 1,072 genera and 48 families, we analyzed genetic differences within and between species and evaluated possible data errors in the insect barcodes. The results showed that errors in the barcode data are not rare, and most of them are human errors, such as misidentification of specimen, sample confusion, and contamination. A large part of the errors are attributed to the inappropriate and imprecise practices in the DNA barcoding workflow. Herein, suggestions are provided to improve the practical operations and workflow of DNA barcoding to reduce human errors.